Transaction Costs and the Pricing of Assets - MAYSHAR, JORAM (Journal of Finance, 1981)
ABSTRACT The existence of transaction costs explains why investors do not fully diversify their portfolios. This paper examines the implications of such limited diversification on equilibrium asset prices in the framework of the capital asset pricing model. In the pricing equation obtained here an asset's risk premium depends on a weighted average of its covariance with the market and its own variance.